Impact of Agricultural Land and the Output of Agricultural Products Moderated with Internet Users toward the Total export of Agricultural Product in Three Islamic South East Asian Countries - Tiara Trenawulan Barkah; Sulistya Rusgianto; Akhmad Kusuma Wardhana (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2022)
Agriculture was the key to preserving the main supply of food. Internet users could moderate the output of agricultural product. This study has a purpose to observe if agricultural land and its products moderated with internet users could affect the total exports of agricultural materials in. This study used secondary data collected from sesric.org and fao.org from three OIC countries, Idonesia, Malaysia, and Brunei. This study used the number of internet users as a moderating variable on the effect of agricultural production which was divided into several types toward exports.The endogenous variable was total export, a moderating variable was the total of internet users, while the agricultural products were exogenous variables. The data were analyzed using moderated regression analysis to observe if the moderating variable affected exogenous variables. The result showed that before the variables such as width of agricultural land, total output of cow’s meat, chicken’s meat,and freshwater fish were being moderated by number of internet users, all of them had no significant effect to total export. It could be concluded that number of internet users could strengthen the effect of two exogenous variables, which was agricultural land and cow’s meat output toward total export.